Design guidelines as ideation tools – a user study on exploring the subjectivity of unit-cell design guidelines. Issue 1 (3rd April 2019) - Fazelpour, Mohammad; Patel, Apurva; Shankar, Prabhu; Summers, Joshua D.
Abstract: A user study is designed and carried out to evaluate the subjectivity of four unit-cell design (UCD) guidelines and demonstrate how inexperienced designers re-design novel unit-cells using the guidelines as ideation tools. UCD guidelines outline a set of instructions on changing important parameters to guide engineers in intentionally redesigning shapes and topologies for unit-cells when considering a desired structural behavior. The subjectivity of the guidelines is evaluated based on the similarities among modified unit-cells as a result of applying guidelines to initial unit-cells. The metric to measure similarity qualitatively is based on topology and shape definitions. The results show there are similarities among the modified unit-cells; however, two guidelines led to generate more diverse modified unit-cells. Furthermore, the effectiveness of the guidelines is demonstrated by conducting comparative simulation studies on the hexagonal honeycomb unit-cell and top modified unit-cells for each guideline. The results of this study demonstrate the guidelines can be used as ideation tools for the conceptual design of novel unit-cells while the novel unit-cells fulfill a conceptual definition of creativity.